High‐Performance and Breathable Polypyrrole Coated Air‐Laid Paper for Flexible All‐Solid‐State Supercapacitors. Issue 21 (7th August 2017) - Chen, Yuanxun; Cai, Kefeng; Liu, Congcong; Song, Haijun; Yang, Xiaowei
Abstract: High‐performance, breathable, conductive, and flexible polypyrrole (PPy) coated paper electrodes are prepared by an interfacial polymerization method using air‐laid paper as a substrate. Owing to the synergistic effect of superior electrical conductivity, high wettability, and the porous architecture, the prepared electrode not only shows an outstanding specific capacitance and rate abilities (3100 and 2579 mF cm −2 at 1 and 20 mA cm −2 for a PPy coated paper electrode), but also exhibits excellent flexibility, wearability, and breathability. Based on these superior features, an all‐solid‐state supercapacitor assembled with the PPy coated paper electrodes shows an outstanding energy density of 62.4 µW h cm −2, remarkable air permeability and excellent flexibility to sustain various deformations. Furthermore, large‐scale fabrication of conductive flexible paper electrode can be easily achieved through this method. Therefore, this work offers a new vision for flexible energy storage. Abstract : High‐performance, breathable, conductive, and flexible polypyrrole coated paper electrodes are prepared by an interfacial polymerization method using air‐laid paper as a substrate. Because of the synergistic effect of superior electrical conductivity, high wettability, and the porous architecture, the fabricated device not only shows excellent supercapacitor performance, but also exhibits excellent flexibility, wearability, and breathability.